DOI: 10.29007/3mn2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Mother Tongue on the Use of Metaphor in English as a Second Language

Abstract: Metaphor has been widely recognized as a central tool of our cognitive apparatus, motivating the widespread use of metaphorical words and expressions in language and discourse. Therefore, it is important for language learners to use metaphors in the target language appropriately. The influence of the mother tongue on the use of metaphors in essays written by Spanish learners of English was analysed. Three corpora were used for this study: the experimental corpus contained 100 essays of Spanish-speaking learner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Littlemore et al (2014) analyzed five essays by German speakers from each of the CEFR levels A2, B1, B2, C1, and C2, finding that the rate of errors in metaphor use was proportionately higher than the error rate overall, at all levels. Analysis of Spanish learners of English at levels B2 and C1 showed fewer errors at the higher level (Iaroslavtseva and Skorczynska, 2017). In Littlemore et al’s (2014) study, an informant who was a native speaker of the learners’ L1 judged many errors in figurative language use to be linked to L1 influence.…”
Section: Theoretical Framework: Categories Of Unconventional Metaphorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Littlemore et al (2014) analyzed five essays by German speakers from each of the CEFR levels A2, B1, B2, C1, and C2, finding that the rate of errors in metaphor use was proportionately higher than the error rate overall, at all levels. Analysis of Spanish learners of English at levels B2 and C1 showed fewer errors at the higher level (Iaroslavtseva and Skorczynska, 2017). In Littlemore et al’s (2014) study, an informant who was a native speaker of the learners’ L1 judged many errors in figurative language use to be linked to L1 influence.…”
Section: Theoretical Framework: Categories Of Unconventional Metaphorsmentioning
confidence: 94%
“…Experimental data with advanced English L1 learners of Korean has shown that L1 has a strong influence on the processing of L2 metaphors, especially when there is relatively little context (Tu¨rker, 2016). Iaroslavtseva and Skorczynska (2017) estimated that around half of the errors their participants made were due to writers having translated from L1; 53% of errors at B2 and 42% at C1. Paris (2018) found that nearly half of all metaphors used by French students in their written English in her study could be attributed to the influence of the corresponding French expression.…”
Section: Error Versus Creativitymentioning
confidence: 99%